APLICATION OF ISM AND ME-MCDM TECHNIQUES FOR THE IDENTIFICATION OF STAKEHOLDERS POSITION AND ACTIVITY ALTERNATIVES TO IMPROVE QUALITY OF GAYO COFFEE - Rachman Jaya, Machfud dan Muhammad Islam (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACT Application of artificial intelligence such as fuzzy logic is one of the ways to handle in the realworld with uncertainty situation like in coffee bean industry in Highland Gayo of Aceh Province. The aims of this study were to apply Fuzzy Multi Expert Multi Criteria Decision Making (MEMCDM) and Interpretatif Stuctural Modelling (ISM) methods in increasing of institutional system and coffee quality. The results of the study shows that for the coffee quality improvement, the importance alternatives were: improvement of agricultural technique, pre-harvest and post harvest technologies, whereas for the institutional system, the key elements were local government, farmers, and middle-man. Keywords: fuzzy-MEMCDM, ISM, institutional, quality of coffee